DESIGN AND CONSTRUCTION OF MICROCONTROLLER BASED POWER BACK DOOR SIMULATOR (xxxx-xxxx, 2024)
One of the innovations in the automotive sector as an effort to increase comfort and safety for users from the middle class to the upper class is the trunk opening and closing mechanism using a microcontroller. Microcontrollers are now an innovation and are in great demand in control system applications. One of the microcontrollers that is widely used is Arduino. Arduino is very popular because it is simple to use and easy to operate according to needs. Electrical energy is the energy produced by the movement of electrons through a conductor. Electrical power is the amount of electrical energy used every second in a circuit. In its development, electronics is a branch of science and technology with the design of device applications involving electrons in various mediums (such as gases and semiconductors). Power Back Door is one of the renewable technologies in vehicles. This advanced technology works by opening and closing the vehicle's trunk door automatically. The results of this research show that the simulator functions well and according to plan. This simulator can work by detecting objects accurately. It is hoped that the implementation of this simulator can become the basis for developing a power back door system in the future.Keywords: Power Back Door, Automotive, Microcontroller, Arduino, Electrical Energy